Introduction And Understanding of The Concept of Income Tax in Order to Improve Awareness of Tax Obligations for High School Students at Raudhatul Ulum Saka Tiga Islamic Boarding School, Ogan Ilir - Muhammad Nazhif Kurdiawan Riza Utama; Khairani Putri Agustin; Alisyah Ramadhani; Ermadiani; Nilam Kesuma (Indonesian Journal of Community Engagement, 2025)
This community service activity was carried out at the Raudhatul Ulum Saka Tiga Islamic Boarding School, Ogan Ilir, involving 40 students from the Integrated Islamic High School as participants. The activity focused on introducing and understanding the concept of Income Tax (PPh) as an effort to foster awareness of tax obligations from an early age. The program was implemented over three days and consisted of three main stages: introduction, application, and evaluation. The introduction stage was conducted through socialization sessions and interactive video presentations explaining the basic concepts and functions of income tax in supporting national development. The application stage included simulations and simple case studies illustrating how income tax is calculated and applied in everyday economic activities. Meanwhile, the evaluation stage involved pre-tests, post-tests, and participant reflections to assess learning progress and attitude changes. The results showed a significant improvement in students’ understanding of the basic concepts of income tax and a growing awareness that paying taxes represents an act of civic and social responsibility. The novelty of this activity lies in its integration of Islamic values within tax education, where the concept of paying taxes was contextualized as part of a Muslim’s moral duty (fardhu kifayah) and contribution to communal welfare. This Islamic-based approach is particularly relevant to the boarding school environment, fostering not only tax literacy but also ethical and spiritual awareness that aligns with national and religious values.